SEMIOTIC ANALYSIS ON GIANT CHARACTER IN JACK THE GIANT KILLER : A FAIRY TALE BY BENJAMIN TABART - ULANDI, MEGA RETINA PUTRI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Structural, Semiotics, Symbol, Fairy tale Fairy tale is the oldest genre of human culture. Its aims are to conveymoral and entertainment. Fairy tale is the reflection of social custom. One ofEnglish Fairy Tale, Jack the Giant Killer consists of moral value and societycustom that represents signs. This research aims to investigate: the kind of symbol found in the Jack the Giant Killer and its relation with English society.This research applies semiotic analysis by Peirce and structural by Propp.Structural narrative by Propp deals with the sequences of event in the fairy tale.The sequences of event is known as function; the act of character. Semiotics is the study of signs. Everything can be signs while it is interpreted as a sign. For further information, sign is divided into three; icon, index and symbol. The symbol is a sign that shows the relation between signified and signifier, and the relation between it are arbitrary.The result of this research based on Peirce’s concept shows there are threeicon finds in this tale; imaginal, diagrammatic and metaphoric icon. The indexical sign is the reason, cause-effect relation that shows the giant as the villain in the tales. The symbolic sign is giant character in this tale is a symbol of powerful and tyrant character of English’ upper-class in 18th century. The signs found in Jack the Giant Killer supported by function of Propp’s structural.The researcher suggests the next researchers who have the same field mustbe more careful when they interpret something as a symbol so that the study willbe more accurate. Making the new concept of problem and make the limitationalso can help the next researcher to focus and make the study better.